Regional Economic Impacts of Cross-Border Infrastructure: A General Equilibrium Application to Thailand and Lao PDR - Peter Warr; Jayant Menon; Arief Anshory Yusuf (Asian Development Bank (ADB), 2009)
A general equilibrium framework is used in this paper to study the regional economic effects of infrastructure improvements designed to reduce the costs of cross-border inter-regional trade. The analysis focuses on the economic benefits from the Second Mekong International Bridge between Mukdahan Province in Thailand and Savannakhet Province in the Lao People's Democratic Republic. The results suggest that in the short-run, the kind of transport cost reductions that are consistent with improvement of inter-regional transport facilities will produce a modest increase in inter-regional trade volumes in both directions and a small increase in real consumption in both regions. Over a longer period of time, the economic benefits to both regions are very much larger, as investors respond to the changed structure of incentives with new capital investments, and as workers move to regions of greater return to their labor. The results do not confirm the common presumption that the benefits from cross-border infrastructure projects occur only, or overwhelmingly, in the richer region.
hdl:11540/1827
Keywords: D58; I32; R40; 330; Cross-border infrastructure; general equilibrium; Thailand; Lao PDR